Complications Following Gender-Affirming Phalloplasty: A NSQIP Review - Hassan, Bashar; Brown, Madyson; Guo, Lily; Ascha, Mona; Jedrzejewski, Breanna; Cohen, Andrew; Corral, Gabriel Del; Liang, Fan (Journal of Reconstructive Microsurgery Open, 2024)
Background Gender-affirming phalloplasty has a complication rate as high as 76.5%. This is the first study to determine the predictors of 30-day complications following phalloplasty using a national registry.Methods The National Surgical Quality Improvement Program database (2012–2021) was queried for transgender men and Current Procedural Terminology codes pertaining to flap or microsurgery procedures to select for single- and first-stage phalloplasty cases. Included were patients with a length of total hospital stay ≥ 5 days and operating time > 4 hours to select for primary phalloplasty cases. The primary outcome was incidence of major and minor complications, and the secondary outcome was indication for unplanned reoperation. Bivariate analysis and multivariate logistic regression were performed to determine significant predictors of complications.Results Of 90 patients, 18 (20.0%) patients developed at least one complication. The most common complication was unplanned reoperation (n = 10, 11.1%) due to hematoma evacuation (n = 3, 30.0% of reoperations, 3.3% of all patients). A total of 43 (47.8%) underwent single-stage phalloplasty, and 47 (52.2%) underwent first-stage phalloplasty. Compared with patients without complications, those with minor complications are more likely to have had single-stage phalloplasty (n = 37 [45.1%], n = 6 [75.0%]; p = 0.145), but the association was not statistically significant. Longer operating time was associated with greater odds of major complications (adjusted odds ratio [aOR] 95% confidence interval [CI] 1.01 [1.002–1.018]). Patients who smoked within 1 year of surgery had 123 times the odds of 30-day minor complications (surgical site infection, urinary tract infection, wound dehiscence, pneumonia) compared with nonsmokers (aOR [CI] 123.3 [1.4– > 100.0]).Conclusion There were no significant differences in complication rates between single- and first-stage phalloplasties. Patients should be counseled about the overall risk of 30-day complications following phalloplasty. Reducing operating time, smoking cessation, and strict preoperative nicotine testing may assist in mitigating odds of 30-day complications following phalloplasty.
Keywords: phalloplasty; complications; predictors; transgender and nonbinary